2022
DOI: 10.3389/fpubh.2022.1029358
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge and awareness of diabetes mellitus, its risk factors, complications, and prevention methods among adults in Poland—A 2022 nationwide cross-sectional survey

Abstract: IntroductionRegular monitoring of public awareness of diabetes is necessary to provide effective educational and preventive strategies. This study aimed to assess (1) public knowledge and awareness of diabetes among adults in Poland, as well as (2) to identify sociodemographic factors associated with public awareness of diabetes.MethodsThis cross-sectional survey was carried out between 24 and 27 June 2022, on a non-probability random quota sample of 1,051 adults in Poland. The questionnaire included ten quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The respondents' levels of knowledge varied significantly due to their personal experience of being a diabetic or having a diabetic person in the family. These results correspond with the results of other studies aimed at assessing the awareness of diabetes-related issues among different patient groups [32,33] and in the general population [34,17] in Poland.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The respondents' levels of knowledge varied significantly due to their personal experience of being a diabetic or having a diabetic person in the family. These results correspond with the results of other studies aimed at assessing the awareness of diabetes-related issues among different patient groups [32,33] and in the general population [34,17] in Poland.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies show that women in Poland are more aware and focused on their health status and more determined to fulfil their health needs actively [27,28]. This disparity can also be explained by the fact that women in Poland live in larger towns and have a higher average level of education [29] -factors often associated with better access to healthcare services and higher awareness of risk factors and symptoms of diseases [17]. Even though in this study none of those…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This nding may be attributed to healthcare inequities, as Sarah's study on the prevalence of selfreported diabetes in the United States suggests that ethnic minorities and individuals with lower education levels are generally less aware of diabetes and have limited access to healthcare [39]. Additionally, the prevalence of self-reported diabetes was found to be high among overweight and obese individuals, highlighting the role of diabetes awareness as a signi cant in uencing factor [40].…”
Section: Discussionmentioning
confidence: 99%
“…The Polish population has a relatively low awareness of diabetes, its risk factors, symptoms, and complications [31]. Although a study conducted in 2022 revealed that the knowledge of diabetes is better than in 2017, it still remains on a rather low level [32]. Most respondents could name only a few risk factors, symptoms, and complications of diabetes.…”
Section: Low Level Of Knowledge About Risk Factors and Symptoms Of Di...mentioning
confidence: 99%